Seasonal variability of phytoplankton photophysiology in the Southern Ocean: an analysis of uncertainties and the impact of assumptions - Ruiters, Lillina (Department of Oceanography, 2026)
Understanding and accurately quantifying primary production in the Southern Ocean is increasingly important due to its central role in global carbon cycling and climate regulation. However, this region remains undersampled, and its sensitivity to environmental change is not yet fully understood. One approach for estimating phytoplankton productivity is through active single-turnover chlorophyll-a fluorescence (ST-ChlF) techniques, such as Fast Repetition Rate fluorometry (FRRf), which infer photosynthetic capacity by measuring the transport of electrons during photosynthesis. While promising, this technique requires the derivation of several photophysiological parameters, and uncertainties in how these are calculated can affect the accuracy and comparability of results. Additionally, environmental forcing plays a direct role in shaping phytoplankton productivity, but disentangling the drivers of variability in phytoplankton photophysiology remains challenging due to the complex and dynamic nature of the Southern Ocean environment. This two-part thesis addresses both methodological and ecological uncertainties using a multi-seasonal dataset collected in the Atlantic sector of the Southern Ocean. The first part evaluates the impacts of key model assumptions and corrections steps used to derive photophysiological parameters from FRRf measurements. Results highlight the importance of using a fitted connectivity coefficient (ρ) when applying the Kolber-Prasil-Falkowski biophysical model to estimate primary photophysiological parameters from fluorescence transients. Furthermore, the dark-regulated σPSII and the light independent model were shown to be the best performing when deriving the secondary photophysiological parameters of electron transport rates. The application of blank and spectral corrections was also essential, particularly in winter when phytoplankton biomass is low. These corrections had a substantial influence on derived photophysiological parameters. The second part of this thesis investigates how seasonal changes in light availability impact phytoplankton photophysiology and pigment allocation. Under low light conditions during autumn and winter, phytoplankton had lower maximal electron transport rate (ETRmax) and showed increased energetic investment in photosynthetic pigments to maximise photosynthetic capacity. In contrast, higher light availability in spring and summer were associated with enhanced photosynthetic capacity driven by increased σPSII and ETRmax. Spring was identified as a transitional season due to the considerable variability in Ek due to the rapid increase in available light between winter and spring. The high ETRmax in summer resulted from an increase in αETR which was in turn driven by higher σPSII as a photoacclimation response to iron limitation in this season. This two-part thesis demonstrates the best approaches for processing single-turnover chlorophyll fluorescence data to minimise errors. In addition, it highlights how the application of active ST-ChlF techniques can be used to interrogate seasonal and regional variability in phytoplankton photophysiology, and how these differences are reflected in diverse phytoplankton photoacclimation mechanisms, which are in turn driven by changes in the availability of light. This contributes to improving estimates of primary production and understanding its variability in the Southern Ocean.